Determinants factors of agriculture in the Danube Delta area - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
An efficient agriculture is a basic branch of a strong economic system, regardless of the country referred to. All the more we can say this in the case of Romania, taking into account the fact that our country enjoys favorable climatic and pedological conditions for the practice of agriculture, at a high level of productivity. Agriculture is a widely debated topic both in specialized papers, published internationally and domestically, and in various national or European research projects. This is also the case of the project included in the Horizon 2020 program, COASTAL-Collaborative Land-Sea Integration Platform, financed by financing contract number 773782, in which agriculture is treated as a reference economic activity of the Danube Delta coastal area, along with rural tourism. In this paper are analyzed factors that have been delimited by specialists and operators in the field as determinants for specific agriculture in the Danube Delta area.
Keywords: Q15; Q57; 330; COASTAL project; Tulcea county; agriculture; rural development